SULITNYA MEMBANGUN DISIPLIN MASYARAKAT (HOW DIFFICULTY TO DEVELOP PEOPLE DISCOPLINE) - suhadi Purwantara (Universitas Negeri Yogyakarta, 2010)
Discipline is the basic character toward success. Some people in this country too much do not discipline. It causes some problems are disadvantage till the killing. Some cases about accident in highway, air crash, explosion of gas, etc are the evident of indiscipline of people. So that is all be responsibility of educational institutional.